Protective effects of dietary Ocimum basilicum and Thymus vulgaris essential oils on growth performance, immune response, and disease resistance following challenge with Aeromonas hydrophila in Nile Tilapia (Oreochromis niloticus) - Salah M. Aly; Heba M. A. Abdelrazek; Nada H. Eidaroos; Samar I. Mostafa; Doaa S. Farid; Noha I. ElBanna; Mohamed Fathi (Fish Physiology and Biochemistry, 2026)

Comprehensive insights and In silico analysis into the emerging role of LincRNAs in lung diseases pathogenesis; a step toward ncRNA precision - Nadia M. Hamdy; Mohamed Bakr Zaki; Nourhan M. Abdelmaksoud; Shereen Saeid Elshaer; Mai A. Abd-Elmawla; Nehal I. Rizk; Doaa Fathi; Ahmed S. Doghish; Ahmed I. Abulsoud (Functional & Integrative Genomics, 2025)
Long non-coding RNAs (lncRNAs) have emerged as essential regulators of gene expression, significantly influencing various biological processes. Approximately half of all lncRNAs are classified as long intergenic non-coding RNAs (lincRNAs), which are situated among coding genes. Recent studies have documented the role of lincRNAs in the pathogenesis of lung diseases, including lung cancer, pulmonary fibrosis, and pulmonary arterial hypertension. These lincRNAs can modulate gene expression through various mechanisms, including epigenetic modifications, transcriptional regulation, and post-transcriptional regulation. By functioning as competing endogenous RNAs (ceRNAs), lincRNAs can affect the activity of microRNAs (miRNAs) and their corresponding target genes. This review delves into the intricate mechanisms by which lincRNAs contribute to the development and progression of various lung diseases. Furthermore, it discusses the potential of lincRNAs as therapeutic targets.